BEING MUSLIM IN METRO MANILA: Diversity of Identity and Political Loyalty - Sefriyono, Sefriyono; Mutin, Sittie Jehanne U; Ashadi, Andri; Zulfis, Zulfis (State Islamic University North Sumatra, 2025)
This study examines how the multiple identities of the Mindanao Muslim minority in Metro Manila influence their loyalty to the Philippine state. Using qualitative methods through Focus Group Discussions and in-depth interviews conducted in Quiapo, Maharlika Village, and Culiat, the research applies Creswell’s qualitative data analysis framework. The findings reveal four key tendencies: (1) reluctance to identify as Filipinos due to historical, cultural, and religious dissonance; (2) prioritization of ethnic and religious over national identity; (3) pragmatic identification as Filipinos for bureaucratic purposes; and (4) successful integration of Islamic, Bangsamoro, and Philippine identities among a small group who perceive no inherent conflict between them. The study contributes to the discourse on Muslim minority identity negotiation by demonstrating that identity pluralism and adaptive negotiation are crucial mechanisms for sustaining minority existence within a dominant national framework